Nuclear Imaging of Glucose Metabolism: Beyond 18F-FDG. (26th March 2019) - Feng, Han; Wang, Xiaobo; Chen, Jian; Cui, Jing; Gao, Tang; Gao, Yongju; Zeng, Wenbin
Abstract : Glucose homeostasis plays a key role in numerous fundamental aspects of life, and its dysregulation is associated with many important diseases such as cancer. The atypical glucose metabolic phenomenon, known as the Warburg effect, has been recognized as a hallmark of cancer and serves as a promising target for tumor specific imaging. At present, 2-deoxy-2-[ 18 F]fluoro-glucose ( 18 F-FDG)-based positron emission tomography/computed tomography (PET/CT) represented the state-of-the-art radionuclide imaging technique for this purpose. The powerful impact of 18 F-FDG has prompted intensive research efforts into other glucose-based radiopharmaceuticals for positron emission tomography (PET) and single-photon emission computed tomography (SPECT) imaging. Currently, glucose and its analogues have been labeled with various radionuclides such as 99m Tc, 111 In, 18 F, 68 Ga, and 64 Cu and have been successfully investigated for tumor metabolic imaging in many preclinical studies. Moreover, 99m Tc-ECDG has advanced into its early clinical trials and brings a new era of tumor imaging beyond 18 F-FDG. In this review, preclinical and early clinical development of glucose-based radiopharmaceuticals for tumor metabolic imaging will be summarized.